Professionalism and humanitarianism in health care delivery - Teuku Jacob, Teuku Jacob (Universitas Gadjah Mada, 1990)
This article defines professionalism relevant to the medical profession and the trend towards deprofessionalization in medicine. Subsequently humanitarianism is described, followed by the nature and causes of dehumanization in medicine. Rehmnanizing efforts are expected to be enhanced by certain on-going trends in the society.The author further presents the issue of human rights, both natural and cultural, and their relation to the right to health care, whence patient rights developed. In this connection the problem of justice in the allocatiOn of health resources is encountered.Private medical practice in itself does not interfere with either professionalism or humanitarianism as long as distributive justice and patient rights arc observed.Lastly, potential future problems related to medical professionalism and humanitarianism are brought into focus, such as the growing urban slums, rural poverty, and opportunity for practice and employment. It is emphatically noted that sporadic medical interventions among underserviced communities are not effective, except from the vantage point of publicity.Key Words: medical professionalism - patient rights - justice in medicine 7 dehumanization - private practice